Compliance in multinational corporations : business risks in bribery, money laundering, terrorism financing and sanctions - Teichmann, Fabian; Sergi, Bruno S. (Emerald Publishing Limited, 2018)
Over the past two decades, the enforcement of anti-bribery, anti-money-laundering and anti-terrorism-financing regulations has become increasingly challenging for multinational corporations. Bribery and money laundering scandals have the potential to take down entire multinational corporations. Frequently, managers in charge of those firms end up facing criminal prosecution and civil lawsuits, and are not equipped with the formal legal training to prevent these phenomena. Compliance in Multinational Corporations explores the historical background of such phenomena as bribery, money laundering, and terrorism financing. Analysing the legal environment based upon international conventions, and including an empirical analysis of 100 expert interviews, it takes an innovative look at the perspectives of both criminals and compliance experts to provide a long-lasting guide for compliance experts. While traditional compliance and financial crime literature focuses on rules, regulations and prevention mechanisms, this book shows how intelligent criminals act. It offers practical advice and concrete guidelines that will address the most pre-eminent compliance challenges. The book will prove an essential resource for compliance managers, academics and professional educators who wish to equip themselves against the significant risks they face.
Keywords: Fraud -- Prevention.; Money laundering -- Prevention.; Terrorism -- Finance -- Prevention.; Business & Economics -- Finance -- General.; Finance & accounting.; elektronické knihy; electronic books